The fear and the angusiness in Sören Kierkegaard - Calcín Figueroa, Eduardo (2017)
Sören Kierkegard was a Danish philosopher, who developed a philosophy of human existence from the perspective of the individual and his subjectivity. From a very young age, he lived surrounded by an oppressive religious atmosphere, which progressively pushed him into a feeling of anguish, melancholy and guilt. He came to regard faith as man’s unique response to a God who reveals himself to express his will. Faith is the only valid subjective response by which man can embrace his own existence. Hefinds in religious feeling the only way to live a dignified existence in the face of the immeasurable that is God. This faith, however, does not have a merely eschatological character but an understanding of life that cannot be given except from faith itself. “Abraham believed though; and believed for this life. Had his faith referred only to a future life, he would have easily stripped himself of everything in order to quickly abandon a world to which he would no longer belong” (Kierkegaard, 1947, p.24)